Chemical Characterization and Antioxidant Activity of Nine Hypericum Species from Greece - Eleni Kakouri; Panayiotis Trigas; Dimitra Daferera; Efstathia Skotti; Petros A. Tarantilis; Charalabos Kanakis (MDPI AG, 2023)
Hypericum L. comprises about 500 species distributed almost worldwide. Research has mainly focused on H. perforatum with confirmed biological activity on the alleviation of depression symptoms, among others. The compounds responsible for such activity are considered naphthodianthrones and acylphloroglucinols. Other Hypericum species are less studied or not studied, and further research is needed to complete the characterization of the genus. In this study we evaluated the qualitative and quantitative phytochemical profile of nine Hypericum species native to Greece, namely H. perforatum, H. tetrapterum, H. perfoliatum, H. rumeliacum subsp. apollinis, H. vesiculosum, H. cycladicum, H. fragile, H. olympicum and H. delphicum. Qualitative analysis was performed using the LC/Q-TOF/HRMS technique, while quantitative data were calculated with the single point external standard method. Additionally, we estimated the antioxidant activity of the extracts using DPPH and ABTS assays. Three species endemic to Greece (H. cycladicum, H. fragile, H. delphicum) were studied for the first time. Our results indicated that all studied species are rich in secondary metabolites, mainly of the flavonoids family, with strong antioxidant activity.